(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2018)
Essential oils have been isolated from different species of Polyalthia. This is the first report on the chemical composition of essential oil isolated from the leaves of P.korintii. The essential oil has been isolated by hydrodistillation method and chemical composition of the oil was determined by GC-MS and GC-FID techniques. Compounds were identified by calculating the relative retention indices, comparing the mass spectrum with the library (NIST&WILEY) and comparing with literature data. Concentration of components present in the oil was determined by matching peaks of GC-FID with that of GC-MS and area normalization technique. The essential oil was found to be rich in monoterpenoids (74.22%) which found in low concentration in the leaves of other species. The major compounds identified in the leafoil were a pinene ( 43.18% ), ,8-pinene(25.5 I%), myrcene (2.72%), ,8-elemene(3.98), ,8-caryophyllene(3.36%), ahumulene(2.I 0%) and caryophyllene oxide( 4.08% ). The isolated essential oil (10µ1) subjected to antimicrobial sensitivity test by disc diffusion method Staphylococcus aureus ATCC25923, E. coli ATCC25922 and in a clinical strain (Klebsiella pneumonia) againstPolymyxin B (I 0µg) as standard. Essential failed to show antimicrobial activity.